Planetary health education in Indian medical curricula - Prasoon Pattanaik; Anandita Pattnaik (The Journal of Climate Change and Health, 2025)
Introduction: This study assesses the state of planetary health education in Indian medical schools and proposes actionable recommendations for enhancement. Materials and Methods: The Planetary Health Report Card (PHRC), an international student-driven metric-based tool, was used to evaluate planetary health content in six report cards from four prominent Indian medical schools. Five key categories were evaluated: planetary health curriculum, interdisciplinary research, community outreach and advocacy, support for student initiatives, and campus sustainability measures. Results: Disparities were found in integrating planetary health into medical education among surveyed schools. While some topics like ''the effect of extreme heat and pollution on health'' were commonly integrated, critical topics such as ''the carbon footprint of healthcare systems'' were often overlooked. Limited interdisciplinary research and community engagement were noted, with insufficient support for student initiatives. However, all schools showed progress in campus sustainability. The National Medical Commission’s curriculum includes only limited content on planetary health. The absence of dedicated coursework and inconsistent implementation has resulted in uneven integration across the country, with much of it depending on individual faculty initiatives. Conclusion: Recommendations include developing dedicated coursework with clear learning outcomes, promoting planetary health research, organizing outreach activities, making educational materials accessible, supporting student initiatives, and enhancing campus sustainability. These recommendations aim to equip future healthcare professionals with the knowledge and skills to address the relationship between human health and planetary well-being, fostering a sustainable healthcare system in India.